Investigation of heat transfer and pressure drop in plate heat exchangers having different surface profiles - Durmus, Aydin; Benli, Hueseyin; Kurtbas, Irfan; Gul, Hasan (Pergamon-Elsevier Science Ltd, 2009)
It would be misleading to consider only cost aspect of the design of a heat exchanger. High maintenance costs increase total cost during the services life of heat exchanger. Therefore exergy analysis and energy saving are very important parameters in the heat exchanger design. In this study, the effects of surface geometries of three different type heat exchangers called as PHEflat (Flat plate heat exchanger), PHEcorrugated (Corrugated plate heat exchanger) and PHEasteriks (Asterisk plate heat exchanger) on heat transfer, friction factor and exergy loss were investigated experimentally. The experiments were carried out for a heat exchanger with single pass under condition of parallel and counter flow. In this study. experiments were conducted for laminar flow conditions. Reynolds number and Prandtl number were in the range of 50 <= Re <= 1000 and 3 <= Pr <= 7, respectively. Heat transfer, friction factor and exergy loss correlations were obtained according to the experimental results. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Heat exchanger; Plate heat exchanger; Laminar flow; Exergy loss